Backstory 5 : Interviews with Screenwriters of the 1990s. - McGilligan, Patrick (University of California Press, 2009)
Patrick McGilligan continues his celebrated interviews with exceptional screenwriters in Backstory 5, focusing on the 1990s. The thirteen featured writers-Albert Brooks, Jean-Claude Carrière, Nora Ephron, Ronald Harwood, John Hughes, David Koepp, Richard LaGravenese, Barry Levinson, Eric Roth, John Sayles, Tom Stoppard, Barbara Turner, and Rudy Wurlitzer-are not confined to the 1990s, but their engrossing, detailed, and richly personal stories create, in McGilligan's words, "a snapshot of a profession in motion." Emphasizing the craft of writing and the process of collaboration, this ne.